2021
DOI: 10.2147/dmso.s291932
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of PDX-1 in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is a metabolic disease characterized by hyperglycemia which is caused by insufficient insulin secretion or insulin resistance. Interaction of genetic, epigenetic and environmental factors plays a significant role in the development of T2DM. Several environmental factors including diet and lifestyle, as well as age have been associated with an increased risk for T2DM. It has been demonstrated that these environmental factors may affect global epigenetic status, and alter the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 124 publications
(156 reference statements)
2
21
0
1
Order By: Relevance
“…This is associated with reduced PDX1 mRNA levels. The same phenomenon is observed in rat insulinoma beta-like cells (INS 832/13) incubated chronically at high glucose concentrations ( 19 , 79 ). Additionally, treatment of human stem cells with the DNA methylation inhibitor, 5-aza-2′-deoxycytidine, increases PDX1 nuclear levels ( 19 , 96 ).…”
Section: Regulation Of Pdx1 Levels By Ros In Beta-cells During Diabetessupporting
confidence: 69%
See 2 more Smart Citations
“…This is associated with reduced PDX1 mRNA levels. The same phenomenon is observed in rat insulinoma beta-like cells (INS 832/13) incubated chronically at high glucose concentrations ( 19 , 79 ). Additionally, treatment of human stem cells with the DNA methylation inhibitor, 5-aza-2′-deoxycytidine, increases PDX1 nuclear levels ( 19 , 96 ).…”
Section: Regulation Of Pdx1 Levels By Ros In Beta-cells During Diabetessupporting
confidence: 69%
“…The same phenomenon is observed in rat insulinoma beta-like cells (INS 832/13) incubated chronically at high glucose concentrations ( 19 , 79 ). Additionally, treatment of human stem cells with the DNA methylation inhibitor, 5-aza-2′-deoxycytidine, increases PDX1 nuclear levels ( 19 , 96 ). Human and mouse pancreatic islets express hundreds of long non-coding RNAs (lncRNAs), some of which are playing important roles in beta-cell differentiation and function.…”
Section: Regulation Of Pdx1 Levels By Ros In Beta-cells During Diabetessupporting
confidence: 69%
See 1 more Smart Citation
“…Pdx1 was an important transcription factor that plays role in the development and function of the β-cell pancreas [16]. In order to know the effect of FETAA on Pdx1 mRNA expression, we carried out a Real-Time PCR analysis.…”
Section: Effect Of Fetaa On Pdx1 Mrna Expressionmentioning
confidence: 99%
“…Human T2DM case-control studies and intervention studies in non-diabetic people showed epigenetic alterations of PDX1, CDKN1A (cyclin-dependent kinase inhibitor 1; involved in cell cycle regulation) and GLRA1 (glycine receptor alpha 1; down-regulation of neuronal excitability) genes which seem to contribute to diabetes (6). An increase in the level of DNA methylation of PDX-1 has been related to a reduced activity in pancreatic islets and a dysregulation of pancreatic b-cells in T2DM (8). CDKN1A overexpression decreases insulin secretion and proliferation (9) and GLRA1 silencing in clonal b-cells reduced glucosestimulated insulin secretion (10).…”
Section: Introductionmentioning
confidence: 99%